2016
DOI: 10.1038/srep25940
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tendon-to-bone healing after anterior cruciate ligament reconstruction using bone marrow-derived mesenchymal stem cells genetically modified with bFGF/BMP2

Abstract: Many strategies, including various growth factors and gene transfer, have been used to augment healing after anterior cruciate ligament (ACL) reconstruction. The biological environment regulated by the growth factors during the stage of tendon-bone healing was considered important in controlling the integrating process. The purpose of this study was to evaluate the effects of bone marrow-derived mesenchymal stem cells (BMSCs) genetically modified with bone morphogenetic protein 2 (BMP2) and basic fibroblast gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…bFGF-modified BMSCs could accelerate healing after anterior cruciate ligament (ACL) reconstruction. Furthermore, previous studies have demonstrated the superiority of using gene transfer to deliver multiple growth factors for treating orthopedic diseases such as osteoarthritis and ACL injuries [34, 35]. Thus, it is reasonable for us to hypothesize that the simultaneous gene transfer of BMP2 and bFGF would synergistically achieve more efficient bone repair than either gene alone.…”
Section: Discussionmentioning
confidence: 99%
“…bFGF-modified BMSCs could accelerate healing after anterior cruciate ligament (ACL) reconstruction. Furthermore, previous studies have demonstrated the superiority of using gene transfer to deliver multiple growth factors for treating orthopedic diseases such as osteoarthritis and ACL injuries [34, 35]. Thus, it is reasonable for us to hypothesize that the simultaneous gene transfer of BMP2 and bFGF would synergistically achieve more efficient bone repair than either gene alone.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, apply directly to promote endogenous stem cells proliferation and differentiation . Secondly, transfect stem cells with adenoviral vector carrying bFGF or BMP‐2 to defective area to continuously produce the proteins . Thirdly, implant biological materials which loaded the transfected stem cells with the overexpression of bFGF and BMP‐2 genes into bone defect area .…”
Section: Introductionmentioning
confidence: 99%
“…The key healing process after ACL reconstruction primarily relies on the integration of the graft with the host bone. Unfortunately, slow and incomplete healing of the tendon-to-bone interface can manifest from inappropriate treatment regimens, which results in knee joint instability, movement dysfunction, cartilage damage and intra-articular meniscus and ultimately leads to inferior functional rehabilitation as well as worsening osteoarthritis of the knee [2,3]. Recently, surgical reconstruction coupled with soft tissue autograft or allograft, including the patellar tendon and hamstring tendon, has become the standard treatment for a torn ACL [4,5].…”
Section: Introductionmentioning
confidence: 99%